Perbandingan Perlindungan Hukum Hak Kekayaan Intelektual Komunal Antara Indonesia dan China - Maya Ruhtiani (Universitas Batanghari Jambi, 2022)
This research entitled A Comparative Study on Legal Protection of Communal Intellectual Property Rights between Indonesia and China aims to analyze the application of legal protection toward communal intellectual property in Indonesia and China. This research is examined using a normative juridical research method. This method uses the legal positivism approach. This study discusses the legal protection system toward communal intellectual property in Indonesia and China, in which legal protection is ratified by intellectual property regulations originating from international treaties. The results show that Indonesia and China both apply the concept of defensive and positive protection by forming laws specifically related to traditional knowledge (sui generis law). However, this concept cannot be applied in Indonesia and China through special laws and regulations regarding traditional knowledge included in the intellectual property system.